Urinary concentrations of phthalates in relation to circulating fatty acid profile in National Health and Nutrition Examination Survey, 2003–2004 and 2011–2012. (October 2020) - Li, Ming-Chieh; Lin, Ching-Yu; Guo, Yue Leon
Abstract: Animal studies have suggested that phthalate exposure alters the fatty acid composition of blood plasma. Therefore, we conducted an epidemiological study to examine whether urinary concentrations of phthalates are correlated with circulating fatty acids in the general US population. The 2003–2004 and 2011–2012 National Health and Nutrition Examination Survey were used in this study. Ten urinary phthalate metabolites and 23 fatty acids were measured. Fatty acid patterns were identified using principal component analysis (PCA) with an eigenvalue greater than 1. A two-step analysis was performed. We first performed multivariable linear regressions to evaluate whether urinary phthalate metabolites were related to the PCA-derived components of blood fatty acid levels. Then we performed multivariable linear regressions to investigate each of the fatty acids that were suggestively correlated with some of the phthalates in PCA. There were 994 participants (51.91% women). As for men, after adjustments for potential confounding factors, MECPP, MEHHP, and ∑DEHP were all positively correlated with gamma -linolenic, myristoleic, and myristic acids; both MEHHP and ∑DEHP were positively correlated with stearic acid; MMP was positively correlated with docosahexaenoic acid. As for women, MMP was negatively correlated with docosanoic, lignoceric, and arachidic acids; MBzP was negatively correlated with docosahexaenoic acid; both MEHP and MCPP were negatively correlated with docosatetraenoic acid; MEHP was negatively correlated with arachidonic acid, and MCPP was negatively correlated with docosapentaenoic-6 acid. Our findings support that phthalates may be correlated with circulating fatty acids. Graphical abstract: Image 1 Highlights: Animal studies have suggested that phthalates altered fatty acid profile. Human studies on the effects of phthalates on circulating fatty acids are limited. Urinary phthalate metabolites are correlated with circulating fatty acids. The observed correlations differ between men and women. This study suggests potential mechanisms for phthalate induced lipid abnormalities. Abstract : The results of this comprehensive analyses suggest that phthalate metabolites may be correlated with circulating fatty acids.